Nutraceutical: moderate dyslipidemia and osteoarticular disease. An useful integrated treatment? - Laurino, Carmen; Palmeri, B.; Fistetto, G.; Esposito, A. (Progress in Nutrition, 2014)
Purpose: We evaluated the efficacy of an Omega 3 fatty acids, Monascus purpureus, quercetin, astaxanthin and vitamin D3 supplement on blood levels of total cholesterol, HDL, LDL and triglycerides (TG) on a sample of subjects affected with moderate modifications of lipid metabolism. Model: 40 subjects (21 men and 19 women) with moderate dyslipidemia [total cholesterol (202-274 mg/dL), HDL cholesterol (37-53 mg/dL), triglycerides (150-234 mg/dL), LDL cholesterol (132-172 mg/dL) and concomitant symptomatic diseases, mostly in muscle-skeletal diseases, were enrolled at the clinic of the second opinion.They were treated orally with a capsule supplement made with hypolipidemic natural products for 20 days. The measurement of the blood lipid profile was performed at the beginning and at the end of treatment. Results: total cholesterol was decreased by 13,2%, LDL cholesterol by 10,4%, and tryglicerides by 13,9%, while the values of HDL cholesterol increased by 16,3%. Conclusions: the compound has been shown to be effective for the treatment of moderate dyslipidemias.